Uncovering the Global Impact of Measuring Stress, Workload, and Environment on Turnover Intentions: Mengungkap Dampak Global melalui Pengukuran Stres, Beban Kerja, dan Lingkungan terhadap Niat Turnover - Andini Farda Sylvia Zuhri; Dewi Andriani (Universitas Muhammadiyah Sidoarjo, 2024)
Employee turnover is a significant concern for organizations, impacting productivity, morale, and ultimately, profitability. This study investigates the influence of work stress, workload, and work environment on turnover intention among employees of CV. Ambassador Jaya Makmur, a cosmetics company located in Sidoarjo, East Java, Indonesia. Utilizing a quantitative approach with hypothesis testing, data was collected from 75 employees through Google Forms questionnaires. The findings reveal that work stress, workload, and work environment have a positive and significant impact on turnover intention. Specifically, high levels of work stress and workload contribute to employees' intention to leave, while unfavorable work environments also increase turnover intentions. The study underscores the importance of addressing these factors to mitigate turnover and enhance employee retention strategies within organizations. These findings provide valuable insights for human resource management practices, emphasizing the need to create conducive work environments and manage work-related stress and workload effectively to reduce turnover rates. Highlight: Work stress influences turnover. High workload increases turnover. Positive work environment reduces turnover. Keyword: Turnover intention, Work stress, Workload, Work environment, Employee retention